Evaluation of Isosorbide Mononitrate for Preinduction of Cervical Ripening: A Randomized Placebo-Controlled Trial. - Ramya Krishnamurthy; P Pallavee; Seetesh Ghose (Tehran University of Medical Sciences, 2015)
Objective:To evaluate the safety and efficacy of Isosorbide mononitrate (IMN) as a cervical ripening agent prior to induction of labour in term pregnant women. Materials and methods: A randomized placebo-controlled study was conducted on 100 term singleton pregnancies planned for induction of labour. The participants were randomly assigned to two groups. One group received 40 mg IMN and the other group received 40mg of placebo kept vaginally. The main outcome of this study was to evaluate the efficacy of IMN in cervical ripening based on the change in modified Bishop score and the effect on time duration between the drug insertion and delivery. Safety of isosorbide mononitrate was assessed by measuring variables related to maternal and neonatal outcomes. Results:Baseline demographic characteristics were similar in both groups. The mean change in modified Bishop score after 2 doses of 40mg IMN was insignificant when compared to placebo. Though IMN shortened the time duration between the drug insertion to delivery when compared to placebo, it was statistically insignificant. The need for oxytocin and 2(nd) ripening agent was less in IMN group when compared to placebo group but statistically this also proved to be insignificant. It was noted that there was an increase in caesarean deliveries in IMN than in placebo group. IMN did not cause any significant change in maternal hemodynamics and adverse side effects. Though NICU admission and stay was less in IMN than in placebo group, it was statistically insignificant. Conclusion:Though IMN did not cause any maternal and neonatal adverse effects, it was found to be inefficient in comparison to placebo as a cervical ripening agent.